2011
DOI: 10.1159/000327252
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Proatherogenic Biochemical Phenotype in Beta Thalassemia Minor and Intermedia

Abstract: The purpose of this study was to focus on pathophysiological mechanisms linking β-thalassemia intermedia (β-TI) and minor (β-TMI) with cardiovascular risk. Iron status, prooxidant-antioxidant balance and lipid profiles in serum, and lipid content in peripheral blood mononuclear cells (PBMCs) were evaluated in 20 β-TMI subjects, 22 β-TI patients and in 30 nonthalassemic blood donors. The mRNA levels of some genes involved in the regulation of iron and cholesterol metabolism were also determined. In β-TI and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
5
1
2
Order By: Relevance
“…They found that TAC was significantly lower in BTM subjects than in controls, while TBARS was significantly higher, with significant differences between the β 0 and β + thalassemia traits 11 . In addition, Lai et al reported higher levels of the pro-oxidant/antioxidant ratio in β-thalassemia intermedia and BTM, compared to controls 21 . Differences with the present study may be due to methodological differences and sensitivity of the methods.…”
Section: Discussioncontrasting
confidence: 69%
“…They found that TAC was significantly lower in BTM subjects than in controls, while TBARS was significantly higher, with significant differences between the β 0 and β + thalassemia traits 11 . In addition, Lai et al reported higher levels of the pro-oxidant/antioxidant ratio in β-thalassemia intermedia and BTM, compared to controls 21 . Differences with the present study may be due to methodological differences and sensitivity of the methods.…”
Section: Discussioncontrasting
confidence: 69%
“…DFO and other iron chelators are commonly used in the treatment of iron overload disorders such as β‐thalassemia . Moreover, β‐thalassemic patients are considered at high atherogenic risk , and interestingly iron chelation therapy may improve arterial function in these patients . Together, these data suggest that iron chelation may constitute a supplement for the prevention or treatment of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a proposition that elevated level of IL-1α along with increased level of TNF-α, can be involved in cardiovascular events in TM (69). In addition, abnormal pulmonary function has been associated with higher level of IL-8 and TGF-β in TM patients (70).…”
Section: Crosstalk Between Immune System and Other Transfusion Relatementioning
confidence: 99%